Hypertextuality of the Slovenian World Wide Web - Petrič, Gregor (Metodološki zvezki, 2004)
The substantial concern of this article is a question to what extent does the contemporary World Wide Web as an information retrieval system reflect key attributes of ideal hypertextual systems. The topic is relevant, since in the literature notions of hypertext and hypertextual systems are accompanied with strong implications not only for the ease and efficacy of access to information, but also for fostering democratisation, augmenting creativity and cooperativeness of human beings. After the brief presentation of the problem the paper focuses on the methodology of analysing this problem - definition of relevant dimensions of hypertext in the World Wide Web, their operationalisation and empirical verification. The latter is presented most thoroughly since it includes a procedure of generating a network of web sites in the Slovenian World Wide Web on the basis of approximately 1.8 million of web pages, identified by search system Najdi.si. After the definition of units and relations, relevant methods and their results are presented in order to assess the hypertextuality of the Slovenian World Wide Web. It is shown that a relatively great proportion of web sites do not follow the expectation of the designers of the World Wide Web technology for it to be a globally interconnected "Docuverse", however, a large minority of web sites are in aggregate reflecting the attributes of ideal hypertext systems. The results can be informative for the global World Wide Web since one of the essential characteristics of the Slovenian World Wide Web have similar distribution to the one assessed in other researches on significantly larger - although not adequate for complete network analysis - proportions of the World Wide Web.
Keywords: Hipertekst_UPORABI_: Nadbesedilo; xxxxx; Internet; Slovenia; Slovenija; informacijska tehnologija; information technology; svetovni splet; računalniška omrežja; nadbesedilo; analiza